Epidemiology of chronic spontaneous urticaria: results from a nationwide, population‐based study in Italy. (15th March 2016) - Lapi, F.; Cassano, N.; Pegoraro, V.; Cataldo, N.; Heiman, F.; Cricelli, I.; Levi, M.; Colombo, D.; Zagni, E.; Cricelli, C.; Vena, G.A.
Summary: Background: Chronic spontaneous urticaria (CSU) is a common skin disease, but there is a paucity of precise epidemiological data on this disease. Objectives: To obtain information on the epidemiology of CSU in Italy. Methods: The data source was the Health Search IMS Health Longitudinal Patient Database. The study population was formed by patients aged ≥ 15 years, registered with a total of 700 general practitioners, homogeneously distributed across Italy. An algorithm based on the International Classification of Diseases, ninth revision, Clinical Modification was used for the identification of patients with CSU. The annual prevalence and incidence rates of CSU over a 12‐year period (2002–2013) were estimated, along with demographic and clinical determinants. Results: The annual prevalence of CSU ranged from 0·02% in 2002 to 0·38% in 2013. The incidence was 0·10–1·50 per 1000 person‐years. For both prevalence and incidence rates, female patients outnumbered male. The risk of CSU was statistically significantly higher in the presence of the following variables: obesity; anxiety, dissociative and somatoform disorders; malignancies; use of immunosuppressive drugs; and chronic use of systemic corticosteroids. History of autoimmune thyroiditis showed a trend towards an increased risk of CSU, though it was not statistically significant. Smoking was associated with a significantly reduced risk of CSU. Conclusions: Our findings on CSU prevalence are consistent with those obtained in previous studies. Furthermore, this large population‐based study provides important information regarding the association of CSU with demographic and clinical determinants, which have been examined in the primary‐care setting. Abstract : What's already known about this topic? Precise information on the epidemiology of chronic spontaneous urticaria (CSU) in Italy is lacking. What does this study add? Annual incidence and prevalence rates of CSU in Italy were calculated from 2002 to 2013 using data from a national database of general practitioners. Demographic and clinical determinants associated with the occurrence of CSU were determined.